Answer:
0.006% probability that the final vote count is unanimous.
Step-by-step explanation:
For each person, there are only two possible outcomes. Either they vote yes, or they vote no. The probability of a person voting yes or no is independent of any other person. So we use the binomial probability distribution to solve this question.
Binomial probability distribution
The binomial probability is the probability of exactly x successes on n repeated trials, and X can only have two outcomes.
![P(X = x) = C_{n,x}.p^{x}.(1-p)^{n-x}](https://tex.z-dn.net/?f=P%28X%20%3D%20x%29%20%3D%20C_%7Bn%2Cx%7D.p%5E%7Bx%7D.%281-p%29%5E%7Bn-x%7D)
In which
is the number of different combinations of x objects from a set of n elements, given by the following formula.
![C_{n,x} = \frac{n!}{x!(n-x)!}](https://tex.z-dn.net/?f=C_%7Bn%2Cx%7D%20%3D%20%5Cfrac%7Bn%21%7D%7Bx%21%28n-x%29%21%7D)
And p is the probability of X happening.
Random voting:
So 50% of voting yes, 50% no, so ![p = 0.5](https://tex.z-dn.net/?f=p%20%3D%200.5)
15 members:
This means that ![n = 15](https://tex.z-dn.net/?f=n%20%3D%2015)
What is the probability that the final vote count is unanimous?
Either all vote no(P(X = 0)) or all vote yes(P(X = 15)). So
![p = P(X = 0) + P(X = 15)](https://tex.z-dn.net/?f=p%20%3D%20P%28X%20%3D%200%29%20%2B%20P%28X%20%3D%2015%29)
In which
![P(X = x) = C_{n,x}.p^{x}.(1-p)^{n-x}](https://tex.z-dn.net/?f=P%28X%20%3D%20x%29%20%3D%20C_%7Bn%2Cx%7D.p%5E%7Bx%7D.%281-p%29%5E%7Bn-x%7D)
![P(X = 0) = C_{15,0}.(0.5)^{0}.(0.5)^{15} = 0.00003](https://tex.z-dn.net/?f=P%28X%20%3D%200%29%20%3D%20C_%7B15%2C0%7D.%280.5%29%5E%7B0%7D.%280.5%29%5E%7B15%7D%20%3D%200.00003)
![P(X = 15) = C_{15,15}.(0.5)^{15}.(0.5)^{0} = 0.00003](https://tex.z-dn.net/?f=P%28X%20%3D%2015%29%20%3D%20C_%7B15%2C15%7D.%280.5%29%5E%7B15%7D.%280.5%29%5E%7B0%7D%20%3D%200.00003)
So
![p = P(X = 0) + P(X = 15) = 0.00003 + 0.00003 = 0.00006](https://tex.z-dn.net/?f=p%20%3D%20P%28X%20%3D%200%29%20%2B%20P%28X%20%3D%2015%29%20%3D%200.00003%20%2B%200.00003%20%3D%200.00006)
0.006% probability that the final vote count is unanimous.
Answer:
y = -4/3x - 1
Step-by-step explanation:
What are the answer choices???
If it's a negative exponent for example -6 the answer would be 1/x^-6. So if x is 10. Then 10^-6 is equal to 1/10^6 (One over ten to the power of 6 or One divided by 10 to the power six)
73/30 is how fast he walked in 3 hours